The use of somatosensory information during the acquisition of independent upright stance - Barela, J. A.; Jeka, J. J.; Clark, J. E. (Elsevier B.V., 1999)
This study investigated developmental changes in the use of a contact surface during the acquisition of upright posture. Standing infants were longitudinally examined at four developmental epochs: pulling to stand (PS); standing alone (SA); walking onset (WO); and 1.5 months post-walking (PW). The results revealed that as standing experience increased the force applied to the contact surface by the hand and the body sway decreased. Applied force and body sway were consistently related in the anterior-posterior direction (r approximate to 0.65). Temporally, body sway led applied force (approximate to 45 ms) at the PS, SA, and WO developmental periods. However, at PW, the temporal relationship reversed and applied force led body sway (approximate to 140 ms). These results indicate that initially infants use surface contact for mechanical purposes but later for orientation information that affords prospective control of posture.
Keywords: posture; development; somatosensory; prospective; infancy